Basiliximab for the therapy of acute T cell–mediated rejection in kidney transplant recipient with BK virus infection: A case report - Chen, Tingting; Li, Xiaoyu; Wang, Jina; Wang, Xuanchuan; Zhu, Tongyu; Rong, Ruiming; Yang, Cheng (Frontiers in Immunology, 2022)
A 66-year-old Chinese man underwent a deceased donor kidney transplantation. Induction-immunosuppressive protocol consisted of basiliximab (BAS) and methyl prednisolone (MP), followed by maintenance immunosuppression with cyclosporin (CsA), mycophenolate mofetil (MMF), and prednisone (PED). The patient’s post-transplantation course was almost uneventful, and the graft was functioning well [serum creatinine (Scr) 2.15 mg/dL]. The MMF and CsA doses were decreased 1-month post-operative as the BK virus activation was serologically positive. His Scr was elevated to 2.45 mg/dL 45 days after the transplant. A graft biopsy showed BKV nephropathy (BKVN) and acute T cell–mediated rejection (TCMR) Banff grade IIA (I2, t2, ptc2, v1, c4d1, g0, and SV40 positive). The conventional anti-rejection therapy could deteriorate his BKVN, therefore, we administered BAS to eliminate activated graft-infiltrating T cells and combined with low-dose steroid. He responded well to the therapy after two doses of BAS were given, and the kidney graft status has been stable (recent Scr 2.1 mg/dL).